2012
DOI: 10.1097/mou.0b013e32835482cc
|View full text |Cite
|
Sign up to set email alerts
|

Image guidance in the focal treatment of prostate cancer

Abstract: Purpose of Review The advent of PSA screening has led to a 7-fold increase in the incidence of prostate cancer (PCa) without a resultant decrease in mortality rate. This has led to the belief that urologists are over-detecting and over-treating the clinically insignificant disease. To maintain the delicate balance between high cancer cure rate and overtreatment, which could potentially lead to unnecessary morbidities, focal therapy (FT) has emerged as the reasonable “middle ground.” In this article, we present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…However, these small lesions most likely do not represent clinically significant prostate cancer. 29,30 Lastly, MP-MRI and MR-US fusion technology requires a high initial investment and technical support. As the technology becomes more readily available, costs may decrease.…”
Section: Discussionmentioning
confidence: 99%
“…However, these small lesions most likely do not represent clinically significant prostate cancer. 29,30 Lastly, MP-MRI and MR-US fusion technology requires a high initial investment and technical support. As the technology becomes more readily available, costs may decrease.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, up to 75% of patients are found to have localised disease . Current whole‐gland therapy offers the highest oncological efficacy in exchange for significant morbidities, which has motivated a growing interest in focal or regional treatment strategies that can achieve comparable oncological efficacy with minimal adverse effects on sexual and urinary function . Multiple phase I focal therapy trials, predominantly using cryotherapy, have shown the feasibility, safety, short‐term oncological control, and minimal adverse effects profile .…”
Section: Introductionmentioning
confidence: 99%
“…Transperineal prostate biopsy using a template-guided approach was the agreed upon standard to qualify a patient for focal therapy, though what constitutes acceptable biopsy findings was not defined by the panel [Gravas et al 2012]. There was also an overall agreement that multiparametric functional magnetic resonance imaging (MRI) and new transrectal ultrasound (TRUS) techniques show promising results in relation to characterizing men with prostate cancer and localizing their tumor, but that the exact role for patient selection needs to be further elucidated through multicenter studies [Hoang et al 2012]. …”
Section: Consensus Statements On Patient Selection For Focal Therapymentioning
confidence: 99%